Protective role of Yougui Yin in experimental knee osteoarthritis: From the perspective of macrophage polarization - Wu, Zhongqing; Xu, Kanna; Chen, Minchang; Wang, Shihao; Ma, Yong (Prostaglandins & other lipid mediators, 2025)
Knee osteoarthritis (KOA) refers to a prevalent musculoskeletal disorder, frequently complicated by substantial pain and physical disability. Yougui Yin (YGY) is a classic Chinese herbal mixture which has demonstrated potential in treating KOA. Considering that, its cryptic mechanism warrants to be deciphered, which is the subject of our present research. In vivo, H&E staining, Alcian blue staining and Masson staining assessed the histomorphology. Commercial kits and ELISA evaluated oxidative stress markers. ELISA also assayed serum inflammatory cytokines. TUNEL staining appraised apoptosis. Western blotting examined cartilage matrix degradation, apoptotic and NLRP3 inflammasome proteins. Immunofluorescence assay estimated macrophage polarization. In vitro, ELISA assayed oxidative stress markers and inflammatory cytokines. Immunofluorescence and flow cytometry assay estimated macrophage polarization. MTT and flow cytometry assays severally measured cell viability and apoptosis. DCFH-DA probe detected ROS formation. RT-qPCR and Western blotting examined chondrocyte markers, apoptotic and pyroptotic genes. YGY significantly eased the histomorphological damage, apoptosis and pyroptosis in the cartilage tissues of KOA mice. Besides, YGY exerted anti-oxidant and anti-inflammatory activities and drove M1-to-M2 polarization of macrophages both in vitro and in vivo. Further, the co-culture of macrophages treated by LPS and serum containing YGY improved the viability, eliminated the apoptosis, pyroptosis, inflammation, oxidative stress and cartilage degradation in TNF-α-exposed chondrocytes co-cultured with LPS-intervened macrophages. Overall, YGY might mediate macrophage polarization to impede the advancement of KOA. •YGY exerted anti-oxidant and anti-inflammatory activities in OA both in vitro and in vivo.•YGY drove M1-to-M2 polarization of macrophages both in vitro and in vivo•YGY might play the protective role in OA via altering macrophage polarization.